2003
DOI: 10.1088/0953-8984/15/49/023
|View full text |Cite
|
Sign up to set email alerts
|

The composite picture of the charge carriers in LaxSrxCuO4(0.063  x  0.11) superconductors

Abstract: Through far-infrared studies of La 2−x Sr x CuO 4 single crystals for x = 0.063, 0.07, 0.09, and 0.11, we found that only ∼0.2% of the total holes participated in the nearly dissipationless normal state charge transport and superconductivity. We have also observed characteristic collective modes at ω ∼ 18 and 22 cm −1 due to the bound carriers in an electronic lattice (EL) state, and the free carriers are massively screened by the EL. Our findings lead us to propose a composite picture of the charge system whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Nernst signal measurements indicated that, in the underdoping regime, the superconducting condensation is established simultaneously with the coherent motion of Cooper pairs along the c-axis, while in the normal state the Nernst effect is of a strict 2D nature [18]. We find that all of the above results are consistent with the recently proposed composite charge model [15] with an intrinsically coherent c-axis charge transport [19].…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Nernst signal measurements indicated that, in the underdoping regime, the superconducting condensation is established simultaneously with the coherent motion of Cooper pairs along the c-axis, while in the normal state the Nernst effect is of a strict 2D nature [18]. We find that all of the above results are consistent with the recently proposed composite charge model [15] with an intrinsically coherent c-axis charge transport [19].…”
supporting
confidence: 89%
“…These anomalies can be understood in light of our recently proposed composite charge model [15] of intrinsic electronic superconducting phases [8]. Recent high-resolution ARPES experiments on our La 2Kx Sr x CuO 4 crystals also revealed complicated charge dynamics in the cuprate.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…This is in contrast to the common notion of the insulating behavior along the c-axis, which was conjectured based on the absence of the caxis plasma edge in the normal state far-IR reflectivity and by the T-dependence of the c-axis resistivity. Since the fraction of the free electrons becomes less than 1 % in underdoped S-LSCO [22] that increases to ~ 2.8 % at optimal doping as found in this work, the c-axis screened plasma frequency is smaller than Γ c , making the c-axis plasma oscillation appear over-damped. In fact the c-axis plasma edge was observed in the normal state c-axis reflectivity for x = 0.07 but not for x ≥ 0.08 even though the c-axis transport is metallic [32].…”
mentioning
confidence: 51%
“…The displayed data in Figure 2 are chosen for T well below T c to insure that the free electron contribution to the ab-plane σ 1 has been transferred to a delta function centered at ω = 0 in the superconducting state. The doping-dependent ab-plane far-IR σ 1 of LSCO reported by Padilla et al 20 and by Dumm et al 15 are displayed in the left column of Figure 2 and those obtained by Kim et al 16,19 in the right column. These two studies are chosen because they exhibit an internal consistency upon doping.…”
Section: Introductionmentioning
confidence: 69%